Incidentalomas endocrinos, más que una imagen - Cordero A., Francisco; Pineda B., Pedro (Revista Hospital Clínico Universidad de Chile, 2017)
Endocrine incidentalomas are nodular lesions located in endocrine glands, diagnosed serendipitously by different image techniques requested for non-endocrine reasons. They can be located in many sites, but this review describes those that compromise pituitary, adrenal and thyroid gland. The main diagnostic challenges of endocrine incidentalomas are discrimination between benign and malignant lesions, and their functional or non-functional endocrine activity. The relevance of adequate image interpretation and associated hormonal study is discussed